2020
DOI: 10.1039/d0cp00404a
|View full text |Cite
|
Sign up to set email alerts
|

Inter-protein interactions govern protein loading into porous vaterite CaCO3 crystals

Abstract: Loading of therapeutic proteins into mesoporous vaterite crystals is driven by inter-protein interactions in bulk solution and inside the crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Together with mild vaterite decomposition conditions, this opportunity opens broader avenues for further utilization of such SERS platforms. Another important advantage of this platform is the ability to selectively locate probe macromolecules inside the microshell pores by pre-loading of the probes into the vaterite crystals; this is especially interesting, because mesopores of vaterite and those of Au microshells are in the same dimension as typical biomacromolecules [40]. Such a host-guest approach for SERS selectivity has several advantages in comparison, for example, with antibody-antigen binding-based techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Together with mild vaterite decomposition conditions, this opportunity opens broader avenues for further utilization of such SERS platforms. Another important advantage of this platform is the ability to selectively locate probe macromolecules inside the microshell pores by pre-loading of the probes into the vaterite crystals; this is especially interesting, because mesopores of vaterite and those of Au microshells are in the same dimension as typical biomacromolecules [40]. Such a host-guest approach for SERS selectivity has several advantages in comparison, for example, with antibody-antigen binding-based techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The core principle of the former synthesis method is the reaction of Ca 2+ and CO 3 2− ions in an aqueous solution to form insoluble precipitate, as shown in Figure 3 [ 53 ]. It has been identified that water [ 54 ], ions [ 55 ], and biomolecules [ 56 ] play an important role in the formation process of calcium carbonate. In regard with water, the mechanism of different routes shown in the Figure 3 is as follows: (i, ii) when solutions are undersaturated with respect to ACC but supersaturated with respect to any other crystalline CaCO 3 phases, the crystalline nuclei will bypass ACC and grow into larger crystals through diffusion and adsorption of Ca 2+ and CO 3 2− ions [ 57 ].…”
Section: Caco 3 Carriersmentioning
confidence: 99%
“…This approach allows for the encapsulation of various bioactive molecules at mild conditions with a controlled loading mechanism (e.g. proteins and enzymes as well as small drugs) [ 15 , 16 , 42 , 43 , 44 , 45 , 46 ] and demonstrates simple methods of release via external stimuli such as temperature and ionic strength [ 47 , 48 ] variations of which are relevant to biomedical applications such as implant coatings [ 49 , 50 ]. It is of note that bioactive molecules can be themselves a solid matrix treated by the layer-by-layer deposition, for instance, protein aggregates [ 51 , 52 ].…”
Section: Modification Of Various Surfaces With Vaterite Cacomentioning
confidence: 99%